Repeat testing of TSH in preterm infant for congenital hypothyroidism. (4th April 2011) - Srinivasan, R; Cheetham, T; Harigopal, S; Wastell, H
Abstract : Background: The recommended screening cut-off for congenital hypothyroidisim (CHT) in the UK is a blood spot Thyroid Stimulating Hormone (TSH) of 10 μ/l but centres use values ranging from 5–10 μ/l. UK guidelines (2005) recommend that the preterm infant (<36 w) should have a second blood spot sample at the equivalent of 36w gestation because of the potential inability of the preterm infant to mount an appropriate TSH response. Objective: To determine the value of the second blood spot screen in preterm infants. Methods: Regional whole blood TSH data in preterm infants (<35 weeks gestation) from a 5 year period (2005–2010) were assessed. The number of infants who had values greater than the local screening threshold (6 μ/l) were identified. Results: A first TSH sample was obtained from 5518 infants (median gestational age 32w, range 22–35), with a second sample obtained from 5134 (32w, range 23–35). In 38 infants, TSH concentration fell from above to below the screening threshold and in six infants values rose to 6–10 μ/l. TSH concentrations fell below 6 μ/l in five of these infants and the remaining baby had a serum TSH of 6.8 μ/l with a normal free thyroxine. Five infants had raised TSH concentrations (>6 μ/l) on both occasions (birth weight 830–2810 g).Three of the five infants had unequivocal hypothyroidism (serum TSH >80 μ/l on second screen). The initial TSH concentration on one of these three infants was 8.5 μ/l (subsequent serum TSH 134.7 μ/l, free thyroxine 10.4 pmol/l, birth weight 2810 g). The remaining two infants (birth weight 830 g and 2760) had an initial TSH of 6.8 and 11 μ with serum values of 19.7 and 8.3 μ/l respectively. Conclusions: A second screening test will detect babies with CHT when a 10 μ/l cut-off is used. Preterm infants with CHT and a respectable birthweight (>2000g) can have a bloodspot TSH less than 10 μ/l on first screen. However a 'once-only' approach using our local cut-off of 6 μ/l may make a second test redundant. The incidence of CHT in preterm infants (<36w) is higher (∼1 in 1100 to 1 in 1800) than the incidence in newborns as a whole (∼1 in 3500).